Examining discourse structures in Chinese and U.S. elementary mathematics classes. (2020) - Wang, Shuai; Perry, Michelle; Mingle, Leigh; McConney, Marc
Highlights: Vertical (teacher-student) discourse prevails in U.S. and Chinese classrooms. Horizontal (student-student) discourse is rare in U.S. and Chinese classrooms. Teacher-facilitated horizontal discourse is more frequent in Chinese than in U.S. classrooms. Students produce the most mathematical talk in teacher-facilitated horizontal discourse. Abstract: Public policy, theory, and empirical research suggest that mathematical learning is supported in U.S. elementary classrooms when students follow "horizontal" discourse patterns. In contrast, in Chinese classrooms, where students have been reported to excel in mathematics, both tradition and expectations necessitate that teachers remain in control and follow "vertical" discourse patterns. The investigation reported here examined these two patterns and an additional, hybrid pattern—teacher-facilitated horizontal discourse—in transcripts from 31 upper elementary U.S. and Chinese fractions lessons. Using a generalized linear mixed model, results indicated that although vertical discourse was the predominant pattern in both samples, horizontal discourse was more common in U.S. classrooms and teacher-facilitated horizontal discourse was more common in Chinese classrooms.